Diagnostic of Students' Misconceptions Motion and Force Material: An Analytical Study Based on Gender Differences - Inayatul Hasanah; Fatimatus Zahroh; Asyrifatun Najiya; Nur Fajirotun Diniaty Achmad; Herlina Mulyastuti; M. Amien Rais; Sunu Wahyudhi (CV. Dharma Samakta Edukhatulistiwa, 2026)
This research is a descriptive qualitative study that aims to identify junior high school students' misconceptions regarding Motion and Force and to analyze gender differences. The research sample consisted of 30 students, namely 15 males and 15 females, from SMP 1 Burneh Bangkalan. The instrument used was the Three-Tier Diagnostic Test, which grouped students' understanding into the categories Know the Concept, Don't Know the Concept, and Misconception. The results showed a fairly high level of misconceptions in several topics. In the MK 3 category, female students showed a 26.2% and male students 26.7% on the topic of Average Speed. In the MK 2 category, the topic of Influence of External Forces had a high level of misconceptions, namely 16.7% in both genders. In the MK 1 category, the topic of Aerodynamics and Friction showed misconceptions of 20.0% in female students and 33.3% in male students. Overall, the gender analysis showed that both genders experienced misconceptions, but with different tendencies in each category.